1969
DOI: 10.1063/1.1664866
|View full text |Cite
|
Sign up to set email alerts
|

S-Matrix Singularity Structure in the Physical Region. I. Properties of Multiple Integrals

Abstract: We obtain the real singularities and corresponding discontinuities of a class of multiple integrals over real contours. Our aim is to give a unified treatment, obtaining, by elementary mathematical methods. both previously known results and some new generalizations. In a subsequent paper the results are applied to unitarity integrals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…(a) (b) [7] Related terms are generated by other terms in the unitarity equation and together they imply a cut in (s, t)-plane with discontinuity given by [8] just as in perturbative quantum field theory (QFT). In a series of three papers (15)(16)(17) with his student, Michael Bloxham, and John Polkinghorne, David was able to extend this approach to show that for physical values of the momenta, unitarity requires scattering amplitudes to be singular on the arcs of curves where Landau (1959) had determined that singularities occur for Feynman diagrams in QFT, and that the discontinuities associated with these singularities are given by the rules obtained for perturbative QFT by Cutkosky (1960).…”
Section: S-matrix Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…(a) (b) [7] Related terms are generated by other terms in the unitarity equation and together they imply a cut in (s, t)-plane with discontinuity given by [8] just as in perturbative quantum field theory (QFT). In a series of three papers (15)(16)(17) with his student, Michael Bloxham, and John Polkinghorne, David was able to extend this approach to show that for physical values of the momenta, unitarity requires scattering amplitudes to be singular on the arcs of curves where Landau (1959) had determined that singularities occur for Feynman diagrams in QFT, and that the discontinuities associated with these singularities are given by the rules obtained for perturbative QFT by Cutkosky (1960).…”
Section: S-matrix Theorymentioning
confidence: 99%
“…by an adjoint representation Higgs field, to a subgroup H = K × U(1)/Z, where Z = K ∩ U(1) is discrete; K can be identified with a 'colour' gauge group and U(1) with electromagnetism. They showed that, for any smooth solution, the magnetic charge g associated with the U(1) factor satisfies the generalized Dirac condition, exp(igQ) ∈ K , [15] where Q is the electric charge operator, which generates the U(1). If k, the element of K defined by [15], equals 1, then this condition is equivalent to the original Dirac condition [12] and this is the case for G = SU(2), where K is trivial.…”
Section: Monopoles and Dualitymentioning
confidence: 99%
See 2 more Smart Citations
“…With colleagues in Cambridge, Olive developed his methods further to describe in some generality the singularities of the S-matrix at real points of the physical region of the Mandelstam variables and the corresponding discontinuities [18]. However, little progress has been made in describing singularities, real or complex, outside the physical region, which would be necessary in order to discuss the validity of the Mandelstam representation.…”
Section: S-matrix Theorymentioning
confidence: 99%